2019
DOI: 10.29089/2019.19.00090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postural stability in children depending on the body mass index

Abstract: Introduction: Obesity is a common health issue among children and adolescents leading to serious consequences later in life. There are reports on postural stability in children in relation to their nutritional status, but there are few studies involving a stabilometric platform. Aim: A comparison of postural stability in children with normal body mass and obese children. Material and methods: The stabilometric study involved 166 subjects. The postural stability evaluation was performed with the use of the Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Studies have shown that in all balance tests on an unstable platform, obese children perform significantly worse compared to their non-obese peers. However, the results showed no differences when a static platform was used to compare the stability of obese children with children of normal body weight [ 45 ]. Lungren et al conducted their research among 246 boys and 190 girls, aged 6–12 years, assessing neuromuscular fitness such as muscle strength, vertical jump height (VJH) and standing unilateral balance, in pre-pubertal children.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in all balance tests on an unstable platform, obese children perform significantly worse compared to their non-obese peers. However, the results showed no differences when a static platform was used to compare the stability of obese children with children of normal body weight [ 45 ]. Lungren et al conducted their research among 246 boys and 190 girls, aged 6–12 years, assessing neuromuscular fitness such as muscle strength, vertical jump height (VJH) and standing unilateral balance, in pre-pubertal children.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses further demonstrated that BMI is not statistically significantly correlated with balance performance in our cohort of 12-to 18-year-olds, nor is it a significant predictor of performance on any of the tests used. According to several studies, obese children are less capable of maintaining balance than children of normal weight [41,42]. On the other hand, when Rusek et al tested the balance of 1137 children aged 7-15 years on the Zebris stabilometric platform, they found that children with a higher BMI had better balance [43].…”
Section: Discussionmentioning
confidence: 99%
“…Also, collecting information about height may be considered to calculate a BMI parameter that may indicate multiple medical conditions in pediatric patients. 18,19…”
Section: Discussionmentioning
confidence: 99%